Return to Play After Periacetabular Osteotomy for Treatment of Acetabular Dysplasia in Adolescent and Young Adult Athletes. (June 2016) - Heyworth, Benton E.; Novais, Eduardo N.; Murray, Kerri; Cvetanovich, Gregory; Zurakowski, David; Millis, Michael B.; Kim, Young-jo
Background: The Bernese periacetabular osteotomy (PAO) is an effective surgical treatment option for symptomatic acetabular dysplasia. Little evidence exists regarding the results of PAO and rates of return to play (RTP) in an athletic population. Hypothesis: The majority of athletes will demonstrate improvements in functional outcome measures, such as the modified Harris Hip Score and Hip Disability and Osteoarthritis Outcome Score, and will be able to return to sports after PAO. Study Design: Case series; Level of evidence, 4. Methods: A comprehensive surgical hip database at an academic referral center was used to identify a subpopulation of athletes on whom PAO was performed. Data analyzed included preceding surgeries, reoperations, and RTP timing and features. Standard pre- and postoperative radiologic parameters and validated functional outcome measures were assessed, and a regression model assessed risk factors for prolonged time to RTP. Results: Of 245 PAOs performed over the 5-year study period, 46 were performed in 41 patients who met inclusion criteria for being an athlete (mean age, 26.2 years; range, 13-41 years; 36 females; 19% of all PAOs), representing a variety of sports. Prior surgery had been performed on 9 hips (20%). Only 1 post-PAO procedure (2%), excision of heterotopic ossification, was performed during the study period. At final follow-up (median, 3.1 years; range, 1.2-4.4 years), significant mean improvements were observed in modified Harris Hip Score (from 71 to 90; P < .001) and Hip Disability and Osteoarthritis Outcome Score (from 64 to 89; P < .001). The University of California–Los Angeles Activity Scale scores were maintained at a high level (range, 8.0-8.2; P = .28). RTP was reported in 80% of patients (37 of 46) at a median of 9 months postoperatively, with increased postoperative pain as the only independent predictor of longer time to RTP. Of these 37 athletes, 27 (73%) returned to the same level, although this was significantly less common ( P = .06) in competitive athletes (11 of 19; 58%) than in recreational athletes (16 of 18; 89%). Among those who did return at the same level, 23 of 27 (85%) were able to maintain this level over time, but this was not significantly different between competitive (8 of 11; 73%) and recreational (15 of 16; 94%) athletes ( P = .27). Conclusion: Most athletic patients undergoing PAO are female patients and show postoperative improvements in function and return to athletic play. However, although there was no decline in overall activity level at a mean of 3 years, self-assessed athletic performance was attained and maintained in approximately one-half of the study population.